Automated Synthesis of Process-Networks by the Integration of P-graph with Process Simulation - Jean Pimentel; Ákos Orosz; Raymond R. Tan; Ferenc Friedler (Chemical engineering transactions, 2020)
Chemical process simulation has become one of the most important tools for the analysis of process networks. The simulation software currently available are not capable of automatically generating the process structure, the designer must provide it as an input for the simulation. This limits the contribution of simulation to the latter stages of design after the structure has been clearly defined. Since the P-graph methodology was originally conceived to generate process structures systematically, it can be used to produce the topology of the problem automatically based on rigorous combinatorial axioms and algorithms. In this work, the properties of two P-graph algorithms are exploited to automatically generate alternative structures in a commercial simulator, conferring the latter an improved capacity to assist during the early stage of design. Initially, the maximal structure generation (MSG) algorithm is employed to identify a rigorous superstructure from the initial set of plausible operating units. The solution structure generation (SSG) algorithm is then used to enumerate all combinatorially feasible processes included in the superstructure. Each process structure is individually exported to Aspen Plus®, where rigorous models are used to simulate its performance. A set of alternative processes ranked by their economic performance can be generated. This integrated methodology is employed in a case study for producing methyl lactate from methanol and lactic acid. This work demonstrates that integration of P-graph with rigorous simulation constitutes an enhanced tool for process synthesis that automates the generation of process alternatives, providing useful information and additional insight of the synthesis problem.